2019
DOI: 10.1038/s41467-019-09546-7
|View full text |Cite
|
Sign up to set email alerts
|

The compressive strength of crumpled matter

Abstract: Crumpling a sheet creates a unique, stiff and lightweight structure. Use of crumples in engineering design is limited because there are not simple, physically motivated structure-property relations available for crumpled materials; one cannot trust a crumple. On the contrary, we demonstrate that an empirical model reliably predicts the reaction of a crumpled sheet to a compressive force. Experiments show that the prediction is quantitative over 50 orders of magnitude in force, for purely elastic and highly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…It is observed that the evolutionary trend of ΔPE total remains roughly the same during the crumpling process regardless of values of D 0 (Figure a) and k θ (Figure b), which implies that the in-plane stiffness plays a relatively minor role in their crumpling behavior. This is generally in line with the previous study showing that the formed ridges associated with in-plane stiffness are the minimal crumples in terms of energy storage compared to other crumples (i.e., bend, fold, and d-cones) . This is characteristically different from the evolution of ΔPE total for different k ϕ (Figure c) and ε LJ (Figure d)the well depth of ΔPE total becomes greater for smaller k ϕ (i.e., more flexible) or larger ε LJ (i.e., more adhesive).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It is observed that the evolutionary trend of ΔPE total remains roughly the same during the crumpling process regardless of values of D 0 (Figure a) and k θ (Figure b), which implies that the in-plane stiffness plays a relatively minor role in their crumpling behavior. This is generally in line with the previous study showing that the formed ridges associated with in-plane stiffness are the minimal crumples in terms of energy storage compared to other crumples (i.e., bend, fold, and d-cones) . This is characteristically different from the evolution of ΔPE total for different k ϕ (Figure c) and ε LJ (Figure d)the well depth of ΔPE total becomes greater for smaller k ϕ (i.e., more flexible) or larger ε LJ (i.e., more adhesive).…”
Section: Resultssupporting
confidence: 89%
“…This is generally in line with the previous study showing that the formed ridges associated with in-plane stiffness are the minimal crumples in terms of energy storage compared to other crumples (i.e., bend, fold, and d-cones). 61 This is characteristically different from the evolution of ΔPE total for different k ϕ (Figure 2c) and ε LJ (Figure 2d) the well depth of ΔPE total becomes greater for smaller k ϕ (i.e., more flexible) or larger ε LJ (i.e., more adhesive). Note that the system reaches a quasi-equilibrium state when ΔPE total reaches a local minimum value.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…30,34,36,38 A recent practical advance has been the establishment of a simple, empirical, scaling rule for describing the compressive load held by a crumpled ball. 34,35,37 If a crumpled ball is compressed between two parallel plates, the force, F cm is related to the plate separation H as: F cm = Ēt 2 (2 R / H ) α ,where Ē is the plane strain modulus of the sheet, t is its thickness, R the radius of the crumpled ball and α is an exponent. Experimentally, the exponent is known to vary from material to material, but does seem to have well defined average values.…”
Section: Introductionmentioning
confidence: 99%
“…A U-shaped scar is found at the tip of a d cone and its formation is the consequence of the sheet avoiding diverging curvatures at the apex. This picture of stress focusing can be generalized to crumpling [7][8][9][10][11][12]: A crumpled configuration is a state occupying a small volume that combines regions approaching developability and localized ridges focusing the stretching deformations.…”
Section: Introductionmentioning
confidence: 99%